(untitled) (Fiep Bulletin - online, 2014)
The objective of this article is to discuss about the formation process of the professional who works in Phisical Education. This professional should be in continued preparation, which includes making interrogations on the reasons of the occurrence and meaning of the facts, so that he/she may act with ethics and professional responsibility.